Impact and Determinants of COVID-19 Pandemic on the Cataract Surgery Rate at a Tertiary Referral Center - AlHilali S; Al-Swailem SA; Albdaya N; Mousa A; Khandekar R (Dove Medical Press, 2022)
Sara AlHilali,1 Samar A Al-Swailem,1,2 Norah Albdaya,2 Ahmed Mousa,2 Rajiv Khandekar2 1Anterior Segment Division, King Khaled Eye Specialist Hospital, Riyadh, Saudi Arabia; 2Research Department, King Khaled Eye Specialist Hospital, Riyadh, Saudi ArabiaCorrespondence: Sara AlHilali, Anterior Segment Division, King Khaled Eye Specialist Hospital, P. O. Box 7191, Riyadh, 11462, Saudi Arabia, Tel +966544017155, Fax +966114829311, Email SaraAlHilali@gmail.comPurpose: Preventive measures to mitigate the spread of coronavirus, minimized workload on health-care systems and redirected resources to COVID-19 patients resulting in a reduction of elective procedures such as cataract surgery. We report the changes in monthly cataract surgery rate and its associated determinants at a tertiary eye hospital during different periods of the pandemic. Studying the impact of COVID-19 pandemic on cataract surgery rate will help health-care policymakers to better understand the barriers to overcome the expected surgical backlog.Methods: A retrospective review of medical records was performed for cataract surgeries from November 2018 to January 2022, five thousand and ninety-two eyes that underwent cataract surgery during different phases of the COVID-19 pandemic were included. The monthly cataract surgery rate (MCSR) was calculated and compared before (Phase 1), during (Phase 2) and after the COVID-19 pandemic (Phase 3 and 4). Changes in monthly cataract surgery rate during and after the pandemic were presented as ratios and compared pre- to post-pandemic levels to evaluate the impact of different determinants.Results: Of 9701 cataract patients, 5092 (52.5%) were operated in P1, 71 (0.73%) in P2, 116 (1.2%) in P3 and 4422 (45.6%) in P4. The MCSR varied significantly based on the degree of visual impairment in the operated and fellow eyes, and by the type of operating surgeon (P < 0.05). Age, gender, laterality, and place of residence were not significantly different throughout the study period. During phase 1135 (2.6%) eyes had rupture of the posterior capsule (PCR), while 6 eyes (8.4%) had PCR in phase 2.Conclusion: The monthly cataract surgery rate declined during the pandemic and has not recovered to pre-pandemic levels. This should alert the key stakeholders to address the identified barriers to surpassing the baseline monthly surgical rate as this is crucial to eliminate the surgical backlog after the pandemic.Keywords: cataract, Covid-19, surgery, rate, backlog